Ophthalmic services during ongoing conflict: the eye health system in Yemen - David McMaster; Mahfouth Abdallah Bamashmus (BMJ Global Health)
There is little information on the provision of ophthalmic services and the eye health system in Yemen. Using the WHO framework for analysing health systems, we aim to assess what is known about the current eye health system in Yemen with ongoing conflict. Financial constraints, transportation difficulties and security instability are barriers for many of Yemen’s people in need of healthcare. The most recent cataract surgical rate reported in 2012 is 2473 operations per million population, with an increase in operations performed in charity eye camps and the private sector. We identify many governorates of Yemen have inadequate ophthalmic resources. We describe the need for short-term solutions to reduce the backlog prevalence of blindness while local infrastructure is rebuilt, and the importance of long-term reconstruction and transition to local ownership with a sustainable workforce and health service as peace is restored.